An inventory-based analysis of Canada's managed forest carbon dynamics, 1990 to 2008 - Stinson, G (Blackwell Publishing Ltd, 2011)
Canada's forests play an important role in the global carbon (C) cycle because of their large and dynamic C stocks. Detailed monitoring of C exchange between forests and the atmosphere and improved understanding of the processes that affect the net ecosystem exchange of C are needed to improve our understanding of the terrestrial C budget. We estimated the C budget of Canada's 2.3 × 10(6) km(2) managed forests from 1990 to 2008 using an empirical modelling approach driven by detailed forestry datasets. We estimated that average net primary production (NPP) during this period was 809 ± 5 Tg C yr(−1) (352 g C m(−2) yr(−1)) and net ecosystem production (NEP) was 71 ± 9 Tg C yr(−1) (31 g C m(−2) yr(−1)). Harvesting transferred 45 ± 4 Tg C yr(−1) out of the ecosystem and 45 ± 4 Tg C yr(−1) within the ecosystem (from living biomass to dead organic matter pools). Fires released 23 ± 16 Tg C yr(−1) directly to the atmosphere, and fires, insects and other natural disturbances transferred 52 ± 41 Tg C yr(−1) from biomass to dead organic matter pools, from where C will gradually be released through decomposition. Net biome production (NBP) was only 2 ± 20 Tg C yr(−1) (1 g C m(−2) yr(−1)); the low C sequestration ratio (NBP/NPP=0.3%) is attributed to the high average age of Canada's managed forests and the impact of natural disturbances. Although net losses of ecosystem C occurred during several years due to large fires and widespread bark beetle outbreak, Canada's managed forests were a sink for atmospheric CO(2) in all years, with an uptake of 50 ± 18 Tg C yr(−1) [net ecosystem exchange (NEE) of CO(2)=−22 g C m(−2) yr(−1)].